Expert Text Analysis in the Inclusion of History and Philosophy of Science in Higher Education: Expert Text Analysis in the Inclusion of History and Philosophy of Science in Higher Education - Pronskikh, Vitaly; Sorina, Galina V. (Science & education, 2022)
The history and philosophy of science (HPS) plays a special role in education. An elective HPS course on the philosophy of scientific experimentation for young scientists and graduate students of natural science is presented. The course bears a pragmatic character, and its main aims include the development of critical thinking (CT), familiarization with philosophical problems in the relevant areas of knowledge, and the cultivation of a taste for reflective, critical analysis, both individual and group based, which contributes to a deeper understanding of the features of scientific practice in the context of modern complex group cooperation. Students are offered a classical HPS program that included debates on the relationship between empiricism and rationalism, the role of Kant’s transcendental philosophy, modern topics associated with the practical success of rationalism in the emergence of modern natural science, and the theory-ladenness of experimentation. Particular attention during the course is paid to the problems of megascience, the inclusion of which is justified by the specifics of the students’ engagement with science, technology, engineering, and mathematics (STEM). Emphasis is placed on the structure and typology of the collective subject in the modern educational process as well as in experimental practice. Lessons on the methodology of expert text analysis (META), which are aimed at the development of critical thinking skills and the creation of an interdisciplinary discussion space, are included in the course and relied on the example of the history and philosophy of high-energy physics to motivate professional reflection. META classes included in the course prepare graduate students for teamwork in big science, proto-megascience, and megascience. The course offers practical recommendations that could be applied to students’ own research and could be useful for practitioners.